EVALUATION OF DIFFERENT PROTEIN PRECIPITATES OF A WILD MUSHROOM, GANODERMA LUCIDUM FOR ANTIBACTERIAL ACTIVITIES AGAINST HUMAN PATHOGENIC BACTERIA - SUNDARAMOORTHY MARIMUTHU; SABARIMANIKANDAN MAHENDRAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present study was to isolate different antibacterial protein precipitates from Ganoderma lucidum against human pathogenic bacteria and to evaluate suitable precipitating agent. Methods: The acid extract was prepared from the aqueous solution of the test mushroom. From separate aliquots of acid extract, antibacterial proteins were precipitated using five different concentrations (10–50%) of ammonium sulfate solutions, 10% trichloroacetic acid (TCA), 80% ethanol and methanol – Chloroform mixture (2:1 ratio). Protein quantification was performed in each stage of purifications. The as-prepared protein precipitates were subjected for antibacterial and hemolytic assays for identification of the active protein precipitate, which in turn was also checked for minimum inhibitory volume (MIV) for all test organisms. Results: The quantity of each protein precipitated by different protein precipitating agents from the acid extract of the test mushroom was found in the range of 2.3–4.8 mg/g wet.wt. Although all the precipitates showed different levels of antibacterial capacities, 10% TCA precipitate was considered as active protein as it yielded the maximum amount of protein (4.8 mg/g.wet.wt) as well as it exhibited burly bactericidal activities at lower volumes of protein solutions subjected (6.3 and 3.2 μl) on all bacterial strains tested with less hemolytic effects. Conclusion: The protein precipitated by 10% TCA from the acid extract of the test mushroom could be developed as a drug candidate for treating infectious diseases caused by pathogenic microbes in human.